The Relationship Between Eating Disorder Behaviors and Social Anxiety Symptoms Among Students of Medicine and Health Sciences Faculty at University of Mataram - Agustine Mahardika; Azizatul Adni; Amany, Zhafirah (Jurnal Biologi Tropis, 2024)
Eating disorders and social anxiety can co-occur. Most individuals with eating disorders also experience social anxiety and social anxiety is the most common type of anxiety disorder among those with eating disorders. The purpose of this study is to determine the relationship between eating disorder behaviors and social anxiety symptoms among medical students. This study used a cross-sectional design. Subjects involved in the study were 105 medical students from the University of Mataram using non-probability consecutive sampling. The students completed questionnaires on eating disorders and social anxiety. The data were analyzed using Spearman’s correlation test through SPSS. In this study, the mean value for body mass index (BMI) was 22.30 kg/m². The results showed that 16.2% tended to experience eating disorders. No relationship was found between eating disorder symptoms and social anxiety symptoms (r = 0.179; p = 0.068, > 0.05). No relationship was found between eating disorder behaviors and social anxiety symptoms among students of medicine faculty at University of Mataram.